Nurse training in primary care: educational actions with people living with Diabetes mellitus - Camila Aparecida Pinheiro Landim Almeida; Jardel Nascimento da Cruz; Débora Rodrigues Fernandes; Lauryanna de Queiroz Silva; Carlos Henrique Ribeiro de Lima; Eliana Campêlo Lago (Universidade Estadual de Maringá, 2017)
Educational actionswith people living with chronic conditions, especially Diabetes mellitus, are a challenge and a necessary strategy in Primary Care, in view of the glycemic balance, the prevention of complications and the improvement of the quality of life. This study aimed to analyze nurse training in educational actions developed in Primary Care with people living with Diabetes mellitus. A qualitative research was conducted with 28 nurses of Primary Care, in Teresina, state of Piauí, Brazil. Data were collected from April to June 2015 through interviews and analyzed by the collective subject discourse technique. The construction of the results was based on four sequential questions made in the interviews, from which emerged 15 central ideas: lectures, group orientation, nursing consultation and home care; theoretical knowledge, practical knowledge, technical knowledge and expertise knowledge; few materials and infrastructure in the basic unit, lack of professional teamwork, reduced workload and little awareness of teachers; and promotion of care and and self-care, family support and prevention of complications. In the analysis of the discourses, it was possible to conclude about the need for Permanent Health Education in Primary Care.